Potential anti-inflammatory activity of low molecular weight heparin in patients with exacerbations of COPD – short report - Rybacka-Chabros, Barabara; Pietrzak, Aldona; Chabros, Paweł; Milanowski, Janusz (Polish Journal of Public Health, 2014)
Introduction. Anti-inflammatory, separate from anti-thrombotic activity of low molecular weight heparin, is still not well documented. Aim. We estimated the influence of enoxaparin on serum levels of tumor necrosis factor alpha, as the pro-inflammatory cytokine, and interleukin-12, as the heparin-binding, anti-inflammatory cytokine, in patients with exacerbations of chronic obstructive pulmonary disease. Material and methods. Seventy-three consecutive patients (48 males, 25 females) aged 56-75 years without thromboembolic history, were enrolled into the study. They were randomized to group who received enoxaparin in one daily dose 40 mg, or to group who did not receive it. Patients receiving oral anti-coagulants were excluded from the study. Using ELISA approach, we evaluated serum levels of tumor necrosis factor-alpha and interleukin-12 at the following periods: before the first dose of enoxaparin, after 7 days of treatment and 14 days of treatment. Serum level of the C-reactive protein was evaluated simultaneously. Results. In enoxaparin recipients statistically significant (p<0.01) decreasing of TNF-alpha serum levels (from 168.33 pg/ml in admission, to 85.67 pg/ml in the end of study) to compare enoxaparine non-recipients, was observed. Interleukin-12 serum levels were significantly higher in enoxaparine recipients both after 7 days (67.46 pg/ml) and 14 days (89.32 pg/ml) of the study (p<0.05). C-reactive proteins serum levels were significantly higher in enoxaparine non-recipients than recipients (p<0.05) in all study period. Conclusions. Enoxaparin in daily dose 40 mg, significantly depressed serum levels of TNF-alpha and promote serum levels of interleukin-12. Enoxaparin administration may be beneficial for the patients with COPD exacerbation during the first 14 days of treatment.